Yorkshire Tales. Third Series : Amusing sketches of Yorkshire Life in the Yorkshire Dialect - Hartley, John, 1839-1915 (Salt Lake City, UT : Project Gutenberg, 2006)
"Yorkshire Tales. Third Series" by John Hartley is a collection of amusing sketches depicting Yorkshire life written during the late 19th century. The book employs the Yorkshire dialect to offer a humorous look at the everyday experiences and characters from its setting, showcasing their unique quirks and conversations. The opening of the collection features several characters, including Sammywell and his wife Mally, who engage in lively dialogue filled with banter and witty observations about life, appearance, and social expectations. The frequent discussions revolve around themes such as vanity, community, and the humorous misunderstandings that arise in everyday circumstances. The sketches also introduce scenarios involving friends and family that highlight the contrasting perspectives on life, showcasing both the mundane and the comically eccentric aspects of Yorkshire society. (This is an automatically generated summary.)
Grimes' New Hat -- Sammywell Sweeps th' Chimley -- Hepsabah's Hat -- Old Dave to th' New Parson -- Sammywell's Eggsperiment -- What came of a Clock Almanac -- Sammywell's Reformation -- Sheffield Smook -- Awr Lad -- Grimes' Galloway -- True Blue; A Romance of Factory Life -- "If aw wor a Woman" -- Sammywell's Soft Snap -- A Bashful Bradfordian -- Th' Owd, Owd Story -- Jim Nation's Fish-shop -- Bob Brierley's Bull Pup -- Troubles and Trials -- Earnin' a Honest Penny -- Th' Next Mornin' -- Christmas Oysters -- Chairley's Coortin -- What a Gallus Button did
Release date is 2006-04-14
Produced by David Fawthrop and Alison Bush
Keywords: English language -- Dialects -- England -- Yorkshire; Yorkshire (England) -- Fiction